Roberto Arlt África (Edición crítica, lecturas y material) - Schmidt-Welle, Friedhelm (Bibliotheca Ibero-Americana, 2023)
Roberto Arlt is considered one of the most important Argentine writers of the first half of the 20th century. Despite his fame as a novelist and author of etchings, his rich production of dramatic works remains little known and little performed on stage in Argentine and international theaters. With this volume we try to alleviate this partial oblivion through the critical edition of one of his most important theatrical pieces: Africa. The edition compares the text published so far with the typewritten version found in the Ibero-Amerikanisches Institut in Berlin and which is part of the Arlt legacy of that institution. But the volume is more than a mere traditional critical edition, since, apart from the two versions, it includes a series of materials that facilitate the understanding of the text and the context through its paratexts. The importance of the piece within Arlt's theatrical production is perceived when considering the number of these paratexts, which include several stories, etchings and photographs that are based on the writer's trip to Europe and North Africa in 1935. All They indicate important changes in the perception of both Argentine society and foreign culture by Arlt himself, a perception that functions as a mirror to understand one's own.